2015
DOI: 10.1016/j.febslet.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

GAPDH binders as potential drugs for the therapy of polyglutamine diseases: Design of a new screening assay

Abstract: a b s t r a c tProteins with long polyglutamine repeats form a complex with glyceraldehyde-3-phosphate dehydrogenase (GAPDH), which enhances aggregation and cytotoxicity in models of Huntington disease. The aim of this study was to develop a novel assay for the screening of anti-aggregation compounds with a focus on the aggregation-promoting capacity of GAPDH. The assay includes a pure Q58 polyglutamine fragment, GAPDH, and a transglutaminase that links the two proteins. The feasibility of the new assay was ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…We propose that novel anti-HD therapies might be developed by first understanding the significance of the roles played by the glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDH) in polyQ aggregation and transport. Work in our lab has shown that GAPDH forms a strong complex with mutant huntingtin and increases its cytotoxicity in cell and animal models of polyQ pathologies [3,4]. We have also shown the GAPDH is found in aggregates formed by proteins released from dying PC-12 cells overexpressing the Q103 repeat.…”
Section: Introductionmentioning
confidence: 65%
“…We propose that novel anti-HD therapies might be developed by first understanding the significance of the roles played by the glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDH) in polyQ aggregation and transport. Work in our lab has shown that GAPDH forms a strong complex with mutant huntingtin and increases its cytotoxicity in cell and animal models of polyQ pathologies [3,4]. We have also shown the GAPDH is found in aggregates formed by proteins released from dying PC-12 cells overexpressing the Q103 repeat.…”
Section: Introductionmentioning
confidence: 65%
“…GAPDH was previously shown to form cytotoxic aggregating complexes with long polyQ repeats in HD in vitro and in Ataxia 3 in vivo models (Lazarev et al . ). We hypothesized that these aggregates were able to migrate from pathogenic cells to other regions of the brain in a prion‐like manner (Ren et al .…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the enzyme significantly increases the lethal effect of polyQ not only in cells over‐producing mHTT (Lazarev et al . ), but also in the culture medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, we suggested previously a critical role for GAPDH aggregation in oxidative stress-induced neuronal cell death both in vitro and in vivo (14, 15, 24, 25). Further, GAPDH aggregation is likely related to the pathogeneses of amyotrophic lateral sclerosis and Huntington's disease (26, 27). However, the detailed mechanisms for cell death induced by GAPDH aggregation in the context of these pathogeneses remain unclear.…”
Section: Introductionmentioning
confidence: 99%